VD_FINDINFO Plainte / 2019 / 51 vom 18. November 2019 - VD Tribunal cantonal (2019)
PLAINTELP, SUSPENSION DE LA PROCÉDURE, CHOSE JUGÉE, REGISTRE DES POURSUITES, PROCÉDÉ TÉMÉRAIRE | 17 LP, 20a al. 2 ch. 5 LP, 20a al. 3 LP, 8a LP, 126 CPC (CH)